2021
DOI: 10.1177/2473974x21994743
|View full text |Cite
|
Sign up to set email alerts
|

Glottic Keratosis: Significance and Identification of Laryngoscopic Findings

Abstract: Objective Glottic keratosis poses a challenge because a decision to biopsy must weigh the likelihood of dysplasia and cancer against the voice outcome after biopsy. We determined the significance of laryngoscopic findings and agreement among clinicians to identify those specific findings. Study Design Retrospective case-control study. Setting Tertiary care university hospital. Methods Adults with glottic keratosis with preoperative office laryngoscopies were included. Preoperative videostroboscopies were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…13 Aberrant microvasculature and erythroplakia have been noted to have significant associations with dysplastic and malignant lesions; however, inter-rater reliability among clinicians to identify such changes was poor. 8 This contrasts to our study, which did not identify differences in the ability of participants to identify vascular abnormalities on flexible laryngoscopy. Interestingly, the overall sensitivity of vascular stippling (a form of vascular aberrancy) and the presence of dysplasia and malignancy was only 51%.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…13 Aberrant microvasculature and erythroplakia have been noted to have significant associations with dysplastic and malignant lesions; however, inter-rater reliability among clinicians to identify such changes was poor. 8 This contrasts to our study, which did not identify differences in the ability of participants to identify vascular abnormalities on flexible laryngoscopy. Interestingly, the overall sensitivity of vascular stippling (a form of vascular aberrancy) and the presence of dysplasia and malignancy was only 51%.…”
Section: Discussioncontrasting
confidence: 92%
“…One would assume that diagnostic accuracy improves with training. However, a study by Anis et al 8 surveyed a group of head and neck surgeons and found poor inter-rater reliability in identifying features associated with carcinoma, such as erythroplakia and aberrant microvasculature. This emphasizes the importance of developing better training tools to prepare and educate the next generation of surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal erythroplakia and leukoerythroplakia (leukoarythroplasia) represent red plaque lesions and white-with-red speckled plaque lesions secondary to increased hypervascularity and vascular dilation. Erythroplakia is considered the most important clinical predictor for either presence of malignancy or progression toward carcinoma [ 92 ]. It is also considered to carry dysplastic and malignant potential [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges in managing VFL is to determine the potential for malignant transformation of the benign and premalignant lesions, and thus to properly assess the need for surgical intervention. The histology and behavior of glottic keratosis can be frustratingly difficult to predict as lesions can present on a spectrum anywhere from completely benign growth to invasive malignancy [ 28 ]. Studies have reported that the clinical diagnosis of leukoplakia represents an approximately 6–7% chance of progressing into carcinoma [ 17 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the clinical diagnosis of leukoplakia represents an approximately 6–7% chance of progressing into carcinoma [ 17 , 29 ]. A macroscopic appearance and its correlation with malignancy are of special interest to clinicians due to the potential for guiding decision-making at the time of the initial laryngoscopic examination [ 28 ]. However, even when a leukoplakia does not show a positive histopathological result for dysplasia, there is a 3.6–30% risk that it could develop into an invasive carcinoma [ 19 ].…”
Section: Discussionmentioning
confidence: 99%